Challenges of Virtual and Open Distance Science Teacher Education in Zimbabwe - Mpofu, Vongai; Samukange, Tendai; Kusure, Lovemore M; Zinyandu, Tinoidzwa M; Denhere, Clever; Ndlovu, Shakespear; Chiveya, Renias; Matavire, Monica; Mukavhi, Leckson; Gwizangwe, Isaac; Magombe, Elliot; Huggins, Nyakotyo; et al. (International Review of Research in Open and Distributed Learning, 2012)
This paper reports on a study of the implementation of science teacher education through virtual and open distance learning in the Mashonaland Central Province, Zimbabwe. The study provides insight into challenges faced by students and lecturers on inception of the program at four centres. Data was collected from completed evaluation survey forms of forty-two lecturers who were directly involved at the launch of the program and in-depth interviews. Qualitative data analysis revealed that the programme faces potential threat from centre-, institution-, lecturer-, and student-related factors. These include limited resources, large classes, inadequate expertise in open and distance education, inappropriate science teacher education qualifications, implementer conflict of interest in program participation, students’ low self-esteem, lack of awareness of quality parameters of delivery systems among staff, and lack of standard criteria to measure the quality of services. The paper recommends that issues raised be addressed in order to produce quality teachers.